World directory of minorities / edited by Minority Rights Group ; preface by Alan Phillips ; contributors, Bridget Anderson ... [et al.]. - Anderson, Bridget.; Anderson, Bridget (Sociologist) (Minority Rights Group International, 1997)
The World Directory of Minorities is an authoritative, concise and up-to-date reference book on the contemporary situation of ethnic, linguistic and religious minorities worldwide. Covering more than 200 states and dependent territories, and over 700 minority groups, this region-by-region and country-by-country study provides a coherent and wide-ranging introduction to international, regional and local minority rights issues, complete with key bibliographical references and listings of organizations active in the field.